Potential of Bitter Melon (Momordica charantia L.) Extract for Chronic Kidney Disease Based on In Vitro Study via TGF/SMADs Signaling, Antioxidant, Antiinflammation, Apoptosis Inducer Activities - Prahastuti, Sijani; Rahardja, Fanny; Wargasetia, Teresa Liliana; Zahiroh, Fadhilah Haifa; Sabrina, Adilah Hafizha Nur; Kusuma, Hanna Sari Widya; Azis, Rizal; Hadiprasetyo, Dhanar Septyawan; Ningrum, Siti Ratu Rahayu; Widowati, Wahyu; Sarwono, Sylvie (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Chronic kidney disease (CKD) is a physiological abnormality in the kidneys whose prevalence is expected to continue to increase. On the other hand, Bitter melon (Momordica charantia L.) is known to have the potential to manage CKD. This study explores the compound content of M. charantia ethanol extract (MCEE) and its potential for CKD based on in vitro assays. To model chronic kidney disease (CKD), SV40 MES-13 (mouse glomerular mesangial) cells were exposed for 3 days to 20 mM glucose. After glucose induction, the cells were subjected with different concentrations of MCEE (Momordica charantia L. ethanolic extract). The chemical profile of MCEE was analyzed using LC/MS-MS. Cell viability was examined through the WST assay, while intracellular ROS and apoptosis levels were measured by flowcytometry. Colorimetry was used to analyze SOD, MDA, and CAT levels. ELISA was used to analyze inflammatory proteins (TGF-β 1, IL-6, TNF-α, IL-1β ) levels. Meanwhile, the relative gene expression of SMAD-2, SMAD-3, SMAD-4, SMAD-7 was examined through qRT-PCR. The results exhibited that MCEE contains cucurbitane p-coumaric, ferulic acid, caffeic acid, gallic acid, chlorogenic acid, and epicatechin. MCEE was also known to be non-toxic to SV40 MES-13 cells. In addition, MCEE reduced intracellular ROS levels, MDA, necrosis levels, and inflammatory proteins, while also regulating SMAD-2, SMAD-3, and SMAD-4 gene expression. MCEE increased levels of CAT, and SOD, and regulated SMAD-7 gene expression in the CKD cells model. The most effective MCEE is MCEE 50 μg/mL. MCEE demonstrated potential as a CKD treatment based on in vitro studies through TGF/SMADs signaling activity, antioxidant, anti-inflammatory, and apoptosis inducer.